Measuring Bacterial Growth Potential of Ultra-Low Nutrient Drinking Water Produced by Reverse Osmosis: Effect of Sample Pre-treatment and Bacterial Inoculum - Sousi, Mohaned; Salinas-Rodriguez, Sergio G.; Liu, Gang; Schippers, Jan C.; Kennedy, Maria D.; van der Meer, Walter (Frontiers in Microbiology, 2020)
Measuring bacterial growth potential (BGP) involves sample pre-treatment and inoculation, both of which may introduce contaminants in ultra-low nutrient water (e.g., remineralised RO permeate). Pasteurisation pre-treatment may lead to denaturing of nutrients, and membrane filtration may leach/remove nutrients into/from water samples. Inoculating remineralised RO permeate samples with natural bacteria from conventional drinking water leads to undesired nutrient addition, which could be avoided by using the remineralised RO permeate itself as inoculum. Therefore, this study examined the effect of pasteurisation and membrane filtration on the BGP of remineralised RO permeate. In addition, the possibility of using bacteria from remineralised RO permeate as inoculum was investigated by evaluating their ability to utilise organic carbon that is readily available (acetate, glucose) or complex (laminarin, gelatin, and natural DOC), as compared with bacteria from conventional drinking water. The results showed that membrane filtration pre-treatment increased (140–320%) the BGP of remineralised RO permeate despite the extensive soaking and flushing of filters (>350 h), whereas no effect was observed on the BGP of conventional drinking water owing to its high nutrient content. Pasteurisation pre-treatment had insignificant effects on the BGP of both water types. Remineralised RO permeate bacteria showed limitations in utilising complex organic carbon compared with bacteria from conventional drinking water. In conclusion, the BGP bioassay for ultra-low nutrient water (e.g., remineralised RO permeate) should consider pasteurisation pre-treatment. However, an inoculum comprising bacteria from remineralised RO permeate is not recommended as the bacterial consortium was shown to be limited in terms of the compounds they could utilise for growth.